PERCEPTIONS ABOUT LANDSCAPE AND GEOTOURISM IN THE COASTAL ZONES OF THE STATE OF MARANHÃO THROUGH THE STUDY OF THE ENVIRONMENT AND FIELD CLASSES - Pereira da Silva, Isaias; Gonçalves dos Santos, Izani; Helena Arcanjo, Silvia (Journal of Interdisciplinary Debates, 2022)
This work is based on practical field activities, linked to the “Coastal Geomorphology” discipline, taught in a condensed form (2018.4) provided for the academic calendar of the Federal University of Maranhão. Emphasis is placed on the pedagogical resources addressed as a form of teaching, with the insertion of practical activities that facilitated and optimized learning, through elements that are essential for the fixation of knowledge by students. In the scope of Geography and other sciences such as Geomorphology, Geology and Oceanography, the analysis and understanding of landscape observations, in a scenario of coastal areas of Maranhão State, with emphasis on the exceptional region of “Lencóis Maranhenses”, in the geotourism route, consisted in a great experience, whose elements deserved to be brought and highlighted here.